Implementation of ISO 9001: 2015 at Indonesian Railways Company: A Narrative Literature Review - Rahmawati, Aprilia; Rosdiana, Dina; Asbari, Masduki (IJOSMAS, 2023)
The purpose of writing this article is a narrative literature review of 3 (three) articles that discuss the analysis of the implementation of ISO 9001: 2015 at PT. Kerta Api Indonesia (PERSERO) to identify and summarize previously published articles without any criticism for the articles being reviewed. The review results show that PT. Kereta Api Indonesia describes the management of railroad asset documents based on ISO 9001: 2015 concerning Quality Assurance Systems in supporting the revitalization program of several railroads in Indonesia. In the process of revitalizing the rail line, of course, documents are needed as the main reference. Asset documents used in the railroad track revitalization activities are documents in the form of technical drawings, asset ownership documents, and cartography. The data used in this research is primary data, obtained from participatory observation in 2019, in-depth interviews, and a review of document asset document management activities.